Pareto improvements by in-kind-transfers - Frank Stähler (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1992)
This paper shows that in-kind-transfers are an effective instrument to stabilize agreements when compliance cannot be guaranteed. It demonstrates the weak superiority of in-kind-transfers for a unilateral relationship between two agents. In particular, it proves that, under conditions of perfect knowledge and necessary selfenforcement of contracts, both agents are at least not worse off by in-kind-transfers compared to monetary payments when no selfenforcing contract exists which,is based on monetary payments. This result holds for finitely and for infinitely repeated games.
Keywords: 330; Spieltheorie; Externer Effekt; Theorie